Strategi Masyarakat Lokal Dalam Mengembangkan Parawisata Di Benang Kelambu - Asrul Umami; Arfinta Maharani; Iska Herlina; Kalis Hayu Wigati; Ika Wijayanti (Jurnal Strategi Bisnis Teknologi, 2024)
This research discusses the development of tourism in Aik Berik Village, which is located in North Batukliang District, Central Lombok Regency, with a focus on Benang Stokel and Benang Kelambu Waterfalls as superior tourist attractions. Tourism in this village has a significant impact on the local community's economy, where this tourism is able to create new jobs for the community. Through community empowerment strategies such as training and digital promotion, local communities play an important role in the management and promotion of tourist destinations. However, the development of this tourism still experiences several challenges in the promotion and accessibility of other destinations. around the Mosquito Net Yarn. In the research carried out, the research used qualitative methods using an approach in the form of case studies, collecting data obtained by interviews, observation and documentation. This research also uses techniques to determine informants using purposive sampling. The main informant is the mosquito net tourism manager, the key informants are tourist motorbike taxi drivers, traders and parking attendants, and the supporting informants are tourists. The data analysis technique used is data reduction. The research results show that active community participation and cooperation between various parties have opened up new economic opportunities and improved community welfare.